Relationship between Employment Status, Income and Compliance with Iron Supplement Tablets with History of Anemia in Pregnant Women - Salsabila, Isma (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2024)
Anemia is a global problem experienced by all countries, especially developing countries. According to the 2018 Basic Health Research data, the incidence of anemia in pregnant women in 2018 was 48.9%, while in 2013 it was 37.1%, increasing by 11.8%. Researchers are interested in conducting research related to "The Relationship between Employment Status, Income, and Compliance with Iron Supplement Tablets with a History of Anemia in Pregnant Women" to determine the factors of the history of anemia in pregnant women. This type of research is quantitative with correlative analytical research using a cross-sectional design. The population used were pregnant women in Mulyasari Village, Ciampel District. The sample in this study was 30 pregnant women with total sampling. The data collection technique used a questionnaire sheet to collect primary data and secondary data through the KIA book. The analysis test used the chi square statistical test. The results of the study showed that there was no relationship between the mother's employment status and the history of anemia in pregnant women (p = 0.850). There is no relationship between family income and history of anemia in pregnant women (p = 0.506). There is a relationship between compliance with iron supplement tablet (TTD) consumption and history of anemia in pregnant women (p = 0.000). Most respondents are aged 20-35 years with the status of housewives, most respondents are already in their third trimester. Based on the results and discussion above, it can be concluded that there is no significant relationship between maternal employment status and family income with history of anemia in pregnant women. There is a relationship between compliance with iron supplement tablet (TTD) consumption and history of anemia in pregnant women.